Media policy in the context of global media flows, the internet, and piracy: an historical analysis of media regulation in Indonesia - Setianto, Yearry Panji (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
Television has been considered one of the most popular media in Indonesia with national television programs as the most dominant for local audiences. Even though imported programs also have been introduced from the early periods of national broadcasting, media regulations in this country tend to limit foreign contents so it does not exceed national contents. However, in recent years national television’s popularity is being challenged not only by global media contents but also by the presence newer media platforms like the Internet. In addition, global media contents are also becoming available through pirated media, such as via VCD, DVD, MP3, and P2P, which are easy to access in many Asian countries due to ineffective regulations against piracy. This study proposes a research question: what are the current media regulations in Indonesia in the discourse of global flows of media contents through the Internet and piracy media? The data gathered mainly from academic literatures, news articles, legislation documents, and online media obtained from Lexis Nexis Academic database The study found that since media regulations in Indonesia mainly focus only in print media and broadcasting, there are few regulations that discuss the threat of global media contents that are mainly accessed through newer media such as the Internet and pirate media outlets. Additionally, lack of socialization of intellectual property rights remains as one of the biggest factors that made any regulations ineffective to overcome media piracy.